EVALUASI PEMBERIAN PAKAN PADA ITIK DENGAN SISTEM PEMELIHARAAN INTENSIF DAN SEMI INTENSIF DI PETERNAKAN RAKYAT (The study of duck feeding management kept under intensive and semi intensive systems by smallholder farmer) - Bonitha Gustin Tumanggor; dwi margi suci; Sri Suharti (Buletin Ilmu Makanan Ternak, 2017)
This experiments aims to study the effect of feeding duck management with extensive and semi intensive system for feed quality, eggs quality and egg production. This experiments used one hundred ducks (intensive) and one hundred ducks semi intensive (fifty ducks in rice field, fifty ducks in the river) that twelve month old. This experiments was conducted in duck raising in Ciherang Village, Bogor Regency. The variables  measured were content of nutrient ration, eggs production and quality of eggs. Production and quality of eggs were analyzed using Anova. The results showed  that  intensive  system  used  commercial  ration  contained  9.85% moisture, 12.89 % crude protein, 9.94% crude fiber, 2.87% fat, 4.35% Ca, and  0.20% P while semi intensive system of duck used commercial ration plus feed from rice field like grain of rice, grass, and unknown material with contained 9.56% moisture, 12.03% crude protein, 10.66% crude fiber, 2.93% fat, 4.41%, Ca and 0.16% P and feed from the river like snails, small crabs, sand, and small stones which contained  9:99 % moisture, 11.76 % crude protein, 11.81% crude fiber, 3.03 % fat, 4:57% Ca, 0:18% P. The system of duck raising did not significantly different  for  quality of eggs.  Production  and  yolk  colour  score  of  egg  in  semi intensive system (in rice field) higher than intensive system P<0.05).